2015
DOI: 10.1016/j.cej.2014.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of zinc by biogenic elemental selenium nanoparticles

Abstract: The adsorption of Zn 2+ ions onto biogenic elemental selenium nanoparticles (BioSeNPs) was investigated. BioSeNPs were produced by reduction of selenite (SeO 3 2− ) in the presence of anaerobic granules from a full scale upflow anaerobic sludge blanket (UASB) reactor treating paper mill wastewater. The BioSeNPs have an iso-electric point at pH 3.8 at 5 mM background electrolyte concentration. X-ray photoelectron spectroscopy showed the presence of a layer of extracellular polymeric substances on the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 50 publications
(57 reference statements)
9
76
0
2
Order By: Relevance
“…S4A). Moreover, the binding energy at 55.3 eV, corresponding to Se 3d, was the characteristic peak for elemental selenium [28], implying that the valence of selenium in the SA-SeNPs and B6-SA-SeNPs was zero (Fig. S4B).…”
Section: Preparation and Characterisation Of Nanoparticlesmentioning
confidence: 95%
“…S4A). Moreover, the binding energy at 55.3 eV, corresponding to Se 3d, was the characteristic peak for elemental selenium [28], implying that the valence of selenium in the SA-SeNPs and B6-SA-SeNPs was zero (Fig. S4B).…”
Section: Preparation and Characterisation Of Nanoparticlesmentioning
confidence: 95%
“…Other applications include antibacterial, antibiofilm (Bartůněk et al 2015;Hariharan et al 2012;Huang et al 2016;Mittal et al 2014;Ramya et al 2015;Shakibaie et al 2015;Tran and Webster 2011;Wang and Webster 2013), antifungal, antiprotozoan, antitapeworm (Bartůněk et al 2015), antiviral, wound healing (Ramya et al 2015), and cytotoxic (Forootanfar et al 2014;Ramya et al 2015) activities. Other non-biological activities such as zinc adsorption (Jain et al 2015), mercury sequestration (Fellowes et al 2011;Jiang et al 2012), biosensing of H 2 O 2 (Wang et al 2010), solar cell (Panahi-Kalamuei et al 2014), and photocatalysis (Triantis et al 2009;Yang et al 2008) are also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Selenite-reducing bacteria have been isolated from a variety of environments including Mono Lake of California (Oremland et al 2004), Dead sea, a salt lake (Oremland et al 2004), Caspian sea of Iran (Shakibaie et al 2015), sediments of Cama-rones river from Atacama desert, Northern Chile (Torres et al 2012), activated sludge (Srivastava and Mukhopadhyay 2013), sludge of Taiyuan sewage plant, China (Li et al 2014), drainage slough from Nevada (Oremland et al 2004), and anaerobic granules from paper mill wastewater treating reactor (Jain et al 2015). In addition, from the soil of a antimony mine from Lengshuijiang, southern China (Zheng et al 2014), soil of a magnesite mine from Salem, India (Ramya et al 2015), soil of a coal mine from West Bengal, India (Dhanjal and Cameotra 2010), selenium laden agricultural soil of North-East Punjab, India (Bajaj et al 2012), soil of mangrove forest from Bhitarkanika, Orissa, India (Mishra et al 2011), rhizosphere soil of a selenium hyperaccumulator legume grown in seleniferous mine from Sardina, Italy (Lampis et al 2014), rhizosphere of wheat grown in herbicide contaminated soil (Dwivedi et al 2013), and rhizosphere of cereal plants grown in ash-derived volcanic soil of southern Chile (Durán et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There is an increased interest in the use of nSe 0 , including applications such as antifungal and anticancer agents (van Cutsem et al 1990;Ahmad et al 2010) as well as an effective agent to prevent and treat Staphylococcus aureus infections (Tran and Webster 2011). Besides, biogenic nSe 0 have been used for the production of high sensitivity sensors (Wang et al 2010) and as potential affinity sorbents for contaminants such as mercury (Fellowes et al 2011) and zinc (Jain et al 2014). Moreover, the influence of Se (as SeO 3 2− ) on the growth and pelletization of P. chrysosporium could be of potential application to control biomass growth in fungal bioreactors.…”
Section: Potential Applicationsmentioning
confidence: 98%